Upconversion luminescence in Tm3+/Yb3+co-doped double-clad silica fibers under 980 nm cladding pumping - Halder, Arindam; Paul, Mukul Chandra; Damanhuri, Siti Sarah Ahmad; Huri, N.A.D.; Hamzah, Azura; Harun, Sulaiman Wadi; Ahmad, Harith; Das, Sourav; Pal, Mrinmay; Bhadra, Shyamal Kumar (Taylor & Francis, 2012)
An investigation is reported of the visible and near-infrared upconversions in Tm 3+/Yb 3+ co-doped double-clad silica fibers (TYDFs) under excitation at 980nm. The TYDFs used were fabricated using the modified chemical vapor deposition (MCVD) and solution doping techniques. Three distinct upconversion luminescences were observed at wavelengths of 482, 649 and 816nm and their intensities found to increase with Yb 3+ concentration. The intensity of blue and red fluorescence bands at 482 and 649nm were found to be the highest with LTY-8 fiber, which had Tm 3+ and Yb 3+ concentrations of 5.610 19 and 15.510 19 ions/cc, respectively. The upconversion luminescence intensity was also observed to decrease with an increase in temperature. The main emission switched from 482nm to 816nm as the temperature increased above 200C.